Strategies And Techniques For Internationalization Of Malaysian Companies - Almarwai, Sahal Ali (2009)
The internationalization process is a very complicated process that is ridden with obstacles and inherent limitations that could compromise the successful internationalization of these companies. The internationalization of a company is a process that can bring large amount of benefits to the company, only if done right. If the wrong strategy is used, the internationalization process would flounder and would be met with little or no success. In essence, employing the wrong strategy could effectively cause the company suffer great losses. Hence, it is very important for the proper strategy to be selected via the use of proper criteria for the selection of strategy of internationalization.